New treatments for the mucopolysaccharidoses: from pathophysiology to therapy - Simona Fecarotta; Serena Gasperini; Giancarlo Parenti (BMC, 2018)
Abstract Enzyme replacement therapy is currently considered the standard of care for the treatment of mucopolysaccharidoses (MPS) type I, II, VI, and IV. This approach has shown substantial efficacy mainly on somatic symptoms of the patients, but no benefit was found for other clinical manifestations, such as neurological involvement. New strategies are currently being tested to address these limitations, in particular to obtain sufficient therapeutic levels in the brain. Intrathecal delivery of recombinant enzymes or chimeric enzymes represent promising approaches in this respect. Further innovation will likely be introduced by the recent advancements in the knowledge of lysosomal biology and function. It is now clear that the clinical manifestations of MPS are not only the direct effects of storage, but also derive from a cascade of secondary events that lead to dysfunction of several cellular processes and pathways. Some of these pathways may represent novel therapeutic targets and allow for development of novel or adjunctive therapies for these disorders.